The praxis of integrated reading and writing instruction on enhancing students’ various aspects of critical thinking and composition skills - Tilahun, Ayalew (Ethiopian Journal of Language, Culture and Communication, 2024)
The purpose of this study was to explore the praxis of integrated reading and writing skills instruction on EFL learners' various forms of critical thinking and composition development at Bahir Dar University. The study used a pretest-posttest/quasi-experimental design, and 96 freshman students (n = 48) as experimental and (n = 48) control groups took part in the study with a random assignment. In this study, the control group was instructed through a skill-separated instructional approach, and the experimental group learned through a newly designed integrated reading and writing instruction for 12 weeks concurrently with three sessions per week, and then, 25 (twenty-five) pre-and post-tests of critical thinking questions were designed to assess students' critical thinking achievement. The Kappa inter-rater and split-half reliability tests were employed to compute the reliability and internal consistency of both tests, respectively. Likewise, a five-paragraph essay was also used to collect data in pre and post-test composition development. Finally, an independent t-test was employed to compute the data, and then the results revealed that both the control and experimental groups were homogeneous regarding their level in the pre-tests of critical thinking and composition skills. However, after the treatment, the results specified that the experimental group outscored the control group significantly on the post-test results. In a nutshell, the study showed the supremacy of integrated reading and writing skills instruction over the conventional approach in enhancing students’ critical thinking and composition skills development.